Metabolic rate and plasma T3 in ad lib. fed and starved muskoxen - Nilssen, K.J.; Mathiesen, S.D.; Blix, A.S. (Rangifer, 1994)
Resting metabolic rate (RMR) in two 12 yrs., semidomesticated, female muskoxen was 0.86 ± 0.10 W • kg-1 in winter, and 1.74 ± 0.27 W • kg-1 in summer, (p<0.001). After 6 days of starvation RMR was down to 0.62 + 0.07 W • kg-1 and 0.77 ± 0.03 W • kg-1 (p<0.001) in winter and summer, respectively. RMR during starvation in winter was 19% below predicted RMR for animals of equal body mass. Standing RMR was significantly higher (p<0.01) than lying RMR. Winter plasma levels of T3 in both animals were 1-1 nmol • l-1 when food was freely available, and 1.4 nmol • l-1 after 6 days of starvation. Plasma concentration of T3 in another 8 free ranging semi-domesticated, female muskoxen aged 12 yrs. in March was 0.64 ± 0.20 nmol • l-1. Corrseponding value in August was 1.00 ± 0.10 nmol • l-1, being significantly higher (p<0.01) than the winter value.